Integrating AI in EFL Classroom: Exploring Students’ Motivation Levels, Teachers’ Perspective and Pedagogical Factors - Nita, Lutfia Rizka; Margana (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to look into the integration of Artificial Intelligence (AI) technology in English as a Foreign Language (EFL) classrooms, with an emphasis on the impact on student motivation, teacher perspectives, and key pedagogical elements. The research uses an embedded design, which includes both qualitative and quantitative data gathering and analysis. This study concludes with recommendations for a balanced approach to AI integration, emphasizing the need for continued support and collaboration among educators, policymakers, and technology developers to improve teaching practices and student results